Phytochemical Analysis and Biological Activities of Ficus racemosa Linn., Myrica esculenta Buch-Ham. Ex D. Don and Urtica dioica Linn. - Maharjan, Sagina; Subba, Bimala (Journal of Institute of Science and Technology, 2023)
Medicinal plants like Ficus racemosa, Myrica esculenta, and Urtica dioica were traditionally used to treat diabetes, cough, fever etc. These plants were collected from Kathmandu and Gorkha district of Nepal and subjected to various biological activities. Methanol extract of all three selected plants when subjected to phytochemical analysis showed the presence of various chemical constituents such polyphenols, flavonoids, tannins, saponins, and glycosides. The methanol extract of F. racemosa bark was found with strongest DPPH radical neutralization activity having IC50 value of 41.48 µg/mL, which was comparable with standard ascorbic acid (31.07 µg/mL). The bark of F. racemosa contained the highest level of total phenolic and total flavonoid contents with the values of 168.89 ± 1.08 mg GAE/g and 41.56 ± 1.83 mg QE/g respectively. The methanol extract of bark of F. racemosa showed high α-amylase inhibitory activity with IC50 value of 164.99 μg/mL. Brine shrimp bioassay showed that the methanol extracts of bark of F. racemosa, bark of M. esculenta, leaves of M. esculenta and U. dioica were lethal to brine shrimp nauplii with LC50 values of 70.79, 177.83, 190.54 and 269.15 µg/mL respectively. Methanol extract of leaves of U. dioica was least active in these biological activities.